Effects of the Occurred Economic Corruption Occurred and the Economic Corruption Control Index on the Economic Growth in Iran - Ezzati, Morteza (International Journal of Economics and Financial Issues, 2017)
This study aimed to estimate the effect of corruption on the economic growth within the framework of endogenous growth model using the occurred economic corruption perceptions index based on the Iranian laws along with the corruption control index and the economy Islamization index. The collected data were related to Iran in 1980-2013 and the growth model was estimated through the logarithmic and linear ordinary least squares (OLS) econometric method. Dependent variables were the gross domestic product (and its growth) and the basic explanatory variables of model, capital, and labor. The occurred economic corruption perceptions index, the corruption control index, and the Islamic economy index have also been considered in the model. The main results indicated that the economic corruption has a negative effect on the growth and the economy Islamization has a positive effect on the growth. The economic growth is reduced to a lesser extent by adding the Islamic economic index to the model for every unit increase in the economic corruption. The corruption control index also showed a significant effect on economic growth. Keywords: occurred economic corruption, corruption control, economic growth, Iran JEL Classifications: C43, O53 O47